Deciphering the antiviral nature of endophytic Bacillus spp. against groundnut bud necrosis virus in cowpea and tomato - Gayathri, M.; Sharanya, R.; Renukadevi, P.; Nakkeeran, S.; Saranya, N.; Varanavasiappan, S.; Raveendran, M.; Suhail, A.; Alkahtani, Saad (Frontiers in Microbiology, 2024)
Tomato, the important vegetable crop is severely affected by Orthotospovirus arachinecrosis which impacts heavy economic losses. Application of insecticide to manage viral disease is not an environmentally safe approach. In view of these issue, we investigated the antiviral efficacy of twentyone bacterial endophytes against GBNV in local lesion host (Cowpea-VBN3). Based on the reduction in lesion number and virus titer as estimated through both DAC ELISA and qPCR in cowpea, the bacterial endophytes viz., Bacillus licheniformis Soya1, Bacillus tequilensis NBL6 and Bacillus velezensis VB7 were selected and further tested in tomato. The study revealed the well-defined antiviral efficacy of these endophytes against GBNV. The percent disease incidence ranged from 16 to 24 percent in endophytes treated tomato plants compared to untreated plants (88 percent). Besides, symptom severity was reduced, application of endophytes also in promotion of the growth compared to untreated control. DAC ELISA revealed that the tomato plants treated with bacterial endophytes challenged with GBNV showed reduction in the virus titer (0.26 -0.39 @ OD 405 nm) at different days of interval after post inoculation (0, 5 and 10 days) compared to untreated control (3.475 @ OD 405 nm). Additionally, reduction in the viral copy number in bacterial endophytes treated plants were evident by real time PCR. Further, tomato plants bacterized with endophytes depicted significant correlation and reduction in viral load and disease incidence as revealed by the principal-component biplot analysis. Thus, the application of bacterial endophytes has a potential role in reducing the disease incidence, severity and titer value of GBNV which will be the promising management approach in future to mitigate the virus infection in tomato plants.